Arquitectos latinoamericanos en la École des Beaux-Arts de París en el siglo XIX (2015)
The purpose of this article is to identify the architects of Latin American origin who studied at the École des Beaux- Arts in Paris in the nineteenth century. The topic has been little discussed in the literature and, when studied, the result has been incomplete. Thus, in order to recognize these professionals, architects enrollment students at the school, where they were identified by their place of origin was consulted. But this relationship is not conclusive because there were other ways to be in the institution were not recorded (introductory courses, students “listeners”, etc.). Either way, the analysis of individual records of registered students allowed to review the mode of their studies, the registration form and its records notes. Thus thirty eight characters were identified, which make up the “official” core of Latin American alumni of the prestigious Parisian institution. Among them we find some of the well-known architects from their own country of origin.